Identifying Indicators of Treatment Satisfaction in Online Therapy Platforms: A Qualitative Study in Taiwan - Ma , Dandan; Wei , Jing (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to identify the core indicators of treatment satisfaction in online therapy platforms from the perspectives of clients in Taiwan.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews. Twenty-two participants (12 women, 10 men), all of whom had engaged in online therapy within the previous year, were purposively recruited. Data collection continued until theoretical saturation was achieved. Interviews were conducted via video call or telephone, lasting between 45 and 70 minutes, and were transcribed verbatim. Thematic analysis was performed using NVivo 14 software, with iterative coding and regular team discussions to ensure reliability and conceptual clarity.Findings: Analysis yielded four major categories of satisfaction indicators. The first, Platform Accessibility and Usability, included ease of access, intuitive navigation, reliability, flexible scheduling, transparent cost structures, and privacy protections. The second, Therapist–Client Relationship, encompassed communication quality, professional competence, trust, rapport building, and responsiveness. The third, Perceived Therapeutic Outcomes, reflected emotional support, cognitive reframing, behavioral improvements, goal attainment, symptom reduction, and long-term benefits. The fourth, Overall User Experience and Satisfaction, involved convenience, perceived value, continuity of care, cultural and language fit, peer recommendation, and comparisons with traditional therapy.Conclusion: The study highlights that treatment satisfaction in online therapy platforms is a multidimensional construct shaped by both digital infrastructure and therapeutic relationships. By integrating technological reliability, therapist empathy, outcome visibility, and cultural resonance, platforms can foster higher satisfaction and sustained engagement.